Maritime liabilities in a global and regional context - Soyer, Bariş; Tettenborn, Andrew (Maritime and transport law library, 2018)
Maritime Liabilities in a Global and Regional Context consists of edited versions of the papers delivered at the Institute of International Shipping and Trade Law's 13th International Colloquium at Swansea Law School in September 2017. Written by a combination of top academics and highly-experienced legal practitioners, these papers have been carefully co-ordinated to give the reader a first-class insight into the issues surrounding maritime liabilities. The book is set out in two parts: - Part I offers a detailed and critical analysis of issues of contemporary importance concerning maritime liabilities - Part 2 discusses contemporary issues concerning the enforcement of maritime liabilities. An invaluable guide to recent legal and practical developments in maritime liabilities, this book is vital reading for both professional and academic readers